Compliance with therapeutic national standards for acute gastroenteritis at a reference Pediatric Hospital in Uruguay (Archives of Pediatrics of Uruguay, 2020)
Introduction: acute gastroenteritis (AGE) is a prevalent disease in childhood. The AGE National Guidelines were published in 2014 in Uruguay, but there are no studies assessing its compliance.Objectives: to determine the degree of compliance with the AGE therapeutic guidelines for the case of children of under 3 years of age admitted at the Pereira Rossell Hospital Center during 2015-2017.Materials and methods: descriptive, retrospective study. All children under 3 years of age hospitalized for AGE were included. Variables: age, hydration level at admission, contraindication for oral administration treatments. Compliance with recommendations was evaluated by comparing the recommended behavior with the one actually adopted in each case, in general and specifically regarding three aspects: hydration plan; nutritional and antimicrobial prescription. Compliance was classified as: good >80%, acceptable 79-60, bad
Keywords: Gastroenteritis; Acute disease; Hospitalized child; Rotavirus